A Review of Hidradenitis Suppurativa (HS): Tinjauan tentang Hidradenitis Suppurativa (HS) - Eftikhaar Hasan Kadhum (Universitas Muhammadiyah Sidoarjo, 2024)
Background: Hidradenitis suppurativa (HS) is a chronic, inflammatory skin disease of the hair follicle, affecting intertriginous areas such as the axillae, perianal, and inguinal regions. It is more prevalent in females, with peak onset between ages 18 and 29. Specific Background: HS, characterized by nodules, abscesses, and sinus tract scarring, uses the Hurley staging system for disease severity classification, but its limitations exist due to its static clinical features. Knowledge Gap: Although several treatment modalities exist, ranging from antibiotics to surgery, there is no definitive therapy, and the pathogenesis remains poorly understood, complicating early diagnosis and management. Moreover, international diagnostic delays of 8-12 years further hinder patient outcomes. Aims: This study aims to explore the limitations of current classification and treatment approaches, while emphasizing the importance of prevention strategies and timely diagnosis to mitigate HS severity. Results: The Hurley classification, though widely used, fails to account for disease progression or quality of life. Current treatment options depend on disease severity, including topical and systemic antibiotics, hormonal therapies, biologics, and surgical interventions. Prevention strategies, such as laser hair removal and lifestyle modifications (e.g., smoking cessation, weight management), are essential to reducing disease impact. Novelty: This research highlights the under-explored role of early prevention and lifestyle interventions in managing HS and reducing progression through Hurley stages. Implications: Enhanced diagnostic tools, combined with early intervention strategies and a holistic approach to patient care, are necessary to improve clinical outcomes, reduce diagnostic delays, and minimize HS-related morbidity. Further research is needed to better understand the genetic and environmental factors contributing to HS pathogenesis. Highlights: HS peaks in females aged 18-29 with chronic skin inflammation. 8-12 years diagnostic delay worsens disease severity and treatment. Prevention: laser hair removal, lifestyle changes reduce HS progression. Keywords: Hidradenitis suppurativa, Hurley staging, inflammatory skin disease, prevention, diagnostic delays